The gospel commission : recovering God's strategy for making disciples - Horton, Michael Scott (Grand Rapids, Mich. : Baker Books, 2011)
"Are we really fulfilling Jesus's final command? Many churches in America today want to be powerful, relevant, and influential in personal and social transformation. A plethora of programs for outreach, discipleship, and spiritual disciplines are available at any bookstore and on countless websites. Yet what we need most is a renewed understanding of and commitment to the Great Commission. We assume that we already know the nature of this commission and the appropriate methods of carrying it out. But Michael Horton contends that it too often becomes our mission instead of God's. At a time when churches are zealously engaged in creating mission statements and strategic plans, he argues that we must ask ourselves anew whether we are ambassadors, following the script we've been given, or building our own kingdoms with our own blueprint. Pastors and church leaders will value this frank and hopeful next-step exploration of the Great Commission as a call to renewed understanding and good practice" -- Publisher description.
Pt. 1. The great announcement. Before you go -- Exodus and conquest : the gospel and the kingdom -- pt. 2. The mission statement. An urgent imperative : "go therefore . . ." -- One gospel and many cultures : contextualization -- The goal : "making disciples" -- pt. 3. The strategic plan. How to make disciples -- Disciples and discipline : "teaching them to observe all that I have commanded" -- The great commission and the great commandment : evangelism and social justice -- Mission creep : inventing our own strategic plan -- Until He comes : the great assurance.
Includes bibliographical references.
Keywords: Discipling (Christianity); Evangelistic work; Missions -- Theory; Mission of the church